Concurrent behavioral and electrophysiological longitudinal recordings for in vivo assessment of aging - Morrone, Christopher Daniel; Tsang, Arielle A.; Giorshev, Sarah M.; Craig, Emily E.; Yu, Wai Haung (Frontiers in Aging Neuroscience, 2023)
Electrophysiological and behavioral alterations, including sleep and cognitive impairments, are critical components of age-related decline and neurodegenerative disease. In preclinical investigation, many refined techniques are employed to probe these phenotypes, but are often conducted separately. Herein, we provide a protocol for a one-time surgical implantation of EMG wires in the nuchal muscle and a skull-surface EEG headcap in mice, capable of 9-to-12-month recording longevity. All data acquisition is wireless, making it compatible with simultaneous EEG recording coupled to multiple behavioral tasks, as we demonstrate with locomotion / sleep staging during home-cage video assessments, cognitive testing in the Barnes maze, and sleep disruption. Time-course EEG and EMG data can be accurately mapped to the behavioral phenotype and synchronized with neuronal frequencies for movement and location to target in the Barnes maze. We discuss critical steps for optimizing headcap surgery and alternative approaches, including increasing the number of EEG channels or utilizing depth electrodes with the system. Combining electrophysiological and behavioral measurements in preclinical models of aging and neurodegeneration has great potential for improving mechanistic and therapeutic assessments and determining early markers of disease.